Alienated in Community: A Personal History of Homophobia and Conversion Therapy. (2nd January 2021) - Williams, Andy
Abstract: In the 1990s, the author—now a transactional analyst, trainer, and supervisor in psychotherapy—became involved in a Christian organization that offered community membership to support sexuality reorientation, also known as conversion therapy. That encounter with alienation compounded the effects of a childhood rife with homophobia. In this essay, the author draws on these lived experiences to identify key cultural and psychological processes that are relevant to his clinical work with clients. He considers the sociological concepts of hostile architecture and callous objects as analogous to the hostile psychosocial environment experienced by LGBTQIA+ children and young people. He proposes that our essential sense of self forms not just in relation to significant others with a deep yearning for acceptance but also requires the challenge of recognizing our fundamental differences from one another. The author argues in favor of a pluralistic philosophy that informs not just professional practice but also the structures we deploy in our broader cultural environment.